Surface-Stiffened Halfspace Under the Action of a Horizontally Directed Mindlin Force - Willner, Kai; Selvadurai, A.P.S. (International Journal of Mechanical Sciences, 2006)
This paper presents an analytical solution to the problem of the interaction between a thin plate that is adhesively bonded to the surface of an isotropic elastic halfspace and a concentrated Mindlin-type force that acts parallel to the bonded surface. The model is an idealization of a surface-stiffened region that has potential applications ranging from mechanics of thin films, thermal barrier coatings, layering created by attrition and wear of surfaces and functionally graded materials. The solution also illustrates the influence of the flexural plate model in mitigating the development of unbounded displacements during the application of localized loading directly at the bonded plate. © 2006 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.tech.FT.FT-TM.surfac_1
Keywords: Adhesively bonded plate; Cerruti's problem; Functionally graded solid; Internal loading of halfspace; Mechanics of thin films; Thermal barrier coatings